Does the association between individual crime propensity and child-to-parent violence vary by family social environment? - Svensson, Robert (Crime & delinquency, 2025)
This study examines whether individual propensity to commit crime and family environment interact in their association with child-to-parent violence (CPV). We assume that individual propensity will be more strongly associated with CPV among those adolescents who are less attached to and controlled by their parents. The study has a cross-sectional design of 4,930 adolescents (age 16 years on average) in southern Sweden. The results support the hypothesis that the association between individual propensity (operationalized as levels of moral values and self-control) and CPV is considerably stronger in family environments that are weak in terms of social cohesion and control. The study shows the importance of moving toward the use of an integrated criminological theoretical model, in the understanding of CPV.